Special education: analysis and actions on initial and continuing teacher education in southern Brazil (Revista Brasileira de Iniciação Científica, 2020)
The objective of this article is to present the results of a research in the scope of scientific initiation, aiming to analyze the actions of training, initial and continuous, of teachers in the field of Special Education. Two studies were analyzed, one with teachers in initial training and another with teachers in continuing training. The results showed the importance of theory being linked to practice and the need to build spaces for continuing education in the school context. We conclude that it is essential to reflect on initial and continuing education with the aim of professional qualification and consequently the teaching and learning process.
Keywords: Special education. Teacher training. Initial formation. Ongoing training.